Association of Lipid Peroxidation with Endothelial Dysfunction in Patients with Overt Hypothyroidism - Tejovathi, B.; Suchitra, M. M.; Suresh, V.; Reddy, V. S.; Sachan, A.; Srinivas Rao, P.V.L. N.; Bitla, A. R. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Hypothyroidism is associated with increased oxidative stress. The mechanism underlying the endothelial dysfunction in thyroid disease is not yet clear. This study aims to investigate lipid peroxidation and its association with endothelial dysfunction in overt hypothyroidism (OHT).Plasma malondialdehyde (MDA) as a marker of oxidative stress and plasma nitrates and asymmetric dimethyl arginine levels (ADMA) as markers of endothelial dysfunction were estimated in 25 OHT patients in comparison to 25 euthyroid controls. Plasma MDA, ADMA levels were significantly increased, whereas plasma nitrates were significantly decreased in the patient group compared to control group (p<0.01). Moreover, a significant positive association between plasma MDA and ADMA was found in the patient group (ρ=0.472, p=0.036). Our results reveal the presence of endothelial dysfunction in OHT patients as evidenced by decreased plasma nitrates and increased ADMA levels. Increased levels of MDA represent an increased generation of reactive oxygen species in these patients. A finding of significant direct relation of plasma MDA with ADMA indicates that oxidative stress has a strong impact on endothelial dysfunction in overt hypothyroidism. Further studies focusing on the role of oxidative stress in endothelial dysfunction and the effects of antioxidant supplementation on endothelial function in OHT patients are required.
Keywords: hypothyroidism; asymmetric dimethyl arginine; malondialdehyde; nitrates; oxidative stress